Assembleia Legislativa e a participação dos evangélicos - Cassotta, Priscilla Leine [UNIFESP] (2011)
This monograph aims to carry out an analysis of political acting by parliament members in connection with pentecostal denominations from 16th legislature of Sao Paulo‟s Legislative Assembly. In this mandate, eight parliament members declared to belong to pentecostal denominations: Andre Soares (DEM), Joao Barbosa (DEM), Jose Bittencourt (PDT), Jose Bruno (DEM), Lelis Trajano (PSC), Marco Porta (PSB), Vaz de Lima (PSDB), Waldir Agnelo (PTB). Since the role of a parliament member is very wide, initially, this monograph intends to draw attention not to the legal action of these members, but the power of not approving the laws. For that, a search in the Sao Paulo‟s Legislative Assembly website was made - www.al.sp.gov.br - where all the content with the parliament votes and their proposals are registered and published. Besides that, the participation of these applications in social networks such as blogs and Twitter was of great importance.